Regional ecological units of northeastern Slovenia - Vovk Korže, Ana (Geografski zbornik, 1996)
Regional ecological units are parts of the geosphere with similar lithological, relief, climate, water, and vegetation characteristics and similar soils. Differential analysis of individual regional elements enables the partition of the landscape into homogenous regional ecological units. In northeastern Slovenia, six different regional ecological units have been defined that differ according to their natural structure and the consequences of anthropogenic encroachment
Keywords: ekosistemi; kulturna krajina; pokrajina; pokrajinska ekologija; Slovenija, severovzhodna; Subdivisions of the Kingdom of Yugoslavia